Nova Niterói: a orla sepultada da utopia à agonia - Martins, Joubert de Assis (2006)
The purpose of this dissertation is to show how the public power and the real estate capital acted as shaping agents of the urban space in the central shore of Niterói, transforming it into support for their plans, projects and other underlying aims, always yielding to the laws of capitalist accumulation and causing, due to this, aggression to the environment, cultural and historical patrimony. The research aims to analyze, retracing some of its antecedents, how this process occurred in the old Fluminense Capital, during the period of 1930 to 1975. In face of the lack of more alert studies about the subject, the research appealed mostly to journals, and also to the gathering of testimony and to the analysis of documents. Shaping agents of the urban space, produced space, landscape and territorial configuration are the main conceptual axis in which the research sustains itself.